ASUPAN VITAMIN A, STATUS VITAMIN A, DAN STATUS GIZI ANAK SEKOLAH DASAR DI KECAMATAN LEUWILIANG, KABUPATEN BOGOR - Marliyati, Sri Anna; Nugraha, Aji; Anwar, Faisal (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2014)
The objective of this research was to study the intake of vitamin A, vitamin A status, nutritional status and health status of primary school children in Leuwiliang Sub—District, Bogor Regency. There were 31 children grade 2 and 3 in SD Angsana I and II Cibeber Village selected by purposive sampling technique. The results showed that more than half of the children had medium sufficient levels of vitamin A (54.8%). Generally, they had normal nutritional status (93.5%). More than half of children had low vitamin A status. The result also found that relationship between the level of adequacy of energy and protein with nutritional status of the children were not significant (p>0.05). The relationship between intake of vitamin A to vitamin A status also showed no significant relationship (p>0.05). It was presumably due to the presence of other factors (food consumption, reserves of vitamin A in the liver, and socio-economic). There was no significant relationship between nutritional status and vitamin A status (p>0.05).